Developing English Description Boxes and Video Promotion for the Reclining Buddha Statue - Artamevia Faberta Elvanda (Jurnal Linguistik Terapan, 2021)
The aim of this research is to make description boxes and video promotion for the Trowulan Reclining Buddha Statue as the first step to attract more international visitors. Video has several advantages in advertising because it combines visual and audio. Thus, it is expected to be able to deliver the messages and attract viewers’ attention. This final project focused on Developing English Description Boxes and A Video Promotion for The Trowulan Reclining Buddha Statue.  The researcher made two products to develop tourism services in the tourist attraction, there were the English description boxes and video promotion. Each product has an important role in developing the tourist attraction. For developing the product, the researcher also supported and helped by Advisors. The English description boxes made by the researcher provided information about some objects or statues in Mahavihara Majapahit. Meanwhile, video promotion has a role in attracting visitors to visit the Reclining Buddha Statue. These combining products will bring good impacts in the tourism industry.